Study of blood serum morphology and homeostasis of rats against acute hypoxia of different genesis under antihypoxant treatment - E. S. Kanaeva; K. A. Pavlova; O. N. Pavlova; O. N. Gulenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Hypoxia is a typical pathologic process, but at present the mechanisms of its profound effect on the organism have not been fully disclosed. Evaluation of serum solid-phase structures in animals under hypoxia may help in understanding the disorders occurring in the body. The multiplicity of pathophysiologic changes in the organism under hypoxia requires the search for effective antihypoxants. The extracts of black currant and medicinal raspberry are promising antihypoxants. The aim of the study was to investigate the morphology of blood serum and the state of homeostasis of rats against the background of acute hypoxia of different genesis with the use of antihypoxants. Object and methods. The study was performed on 480 white mongrel rats. The animals were divided equally into 16 groups. According to group affiliation, animals received intragastrically extracts of black currant, medicinal raspberry, a mixture of these extracts in the ratio of 1:1 and cytochrome C, which was administered intramuscularly, for 15 days. Models of hemic, histotoxic and hypoxic normobaric hypoxia were used. Blood was taken from rats to study the structures of the solid phase of serum by the method of wedge dehydration (formation of dry film - facies) using the diagnostic kit “Lithos-System” with the help of microscope MZ12 “Leica” and video camera “Leica DFC 490” and analyzed digital images. Results. The obtained experimental data indicate pronounced differences in protective-adaptive reactions of the rat organism to acute hypoxia of different genesis, but the introduction of antihypoxants into the organism contributes to the reduction of negative consequences of hypoxia fusion and the highest efficiency is demonstrated by a mixture of extracts of medicinal raspberry and black currant in the ratio 1:1.